2017
DOI: 10.1055/s-0042-121605
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Randomized, Controlled Trials on the Effect of Exercise on Serum Leptin and Adiponectin in Overweight and Obese Individuals

Abstract: Previous reports have shown that exercise improves serum leptin and adiponectin abnormalities in overweight and obese individuals; however, results to date are controversial. Here we performed a systematic review and meta-analysis of the available randomized controlled trials (RCTs) of the possible beneficial action of exercise on serum leptin and adiponectin levels in overweight and obese individuals. We searched PubMed, EMbase, The Cochrane Library, and the Clinicaltrial.gov databases for relevant studies pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 56 publications
(90 reference statements)
7
54
2
1
Order By: Relevance
“…A recent meta-analysis indicated that exercise, particularly aerobic exercise, significantly increased the ADP levels compared to no exercise as well as control in overweight and obese individuals [68], consistent with the finding in T2DM [69]. However, some studies is contrary to the results presented before suggested that the plasma ADP levels were not altered after 12 weeks' combined training in overweight and obese children [70].…”
Section: Adp and Exercisesupporting
confidence: 53%
“…A recent meta-analysis indicated that exercise, particularly aerobic exercise, significantly increased the ADP levels compared to no exercise as well as control in overweight and obese individuals [68], consistent with the finding in T2DM [69]. However, some studies is contrary to the results presented before suggested that the plasma ADP levels were not altered after 12 weeks' combined training in overweight and obese children [70].…”
Section: Adp and Exercisesupporting
confidence: 53%
“…Second, the contribution of exercise has been more difficult to understand, and findings on the effects of increased PA on serum adipokine levels continue to be debated [37]. A few meta-analyses found that there were no statistically significant changes in certain circulating levels of adipokine, such as adiponectin or resistin, in the intervention group with and without exercise [37,38]. Divergent forms of exercise may have varying effects on adipokine levels [39].…”
Section: Discussionmentioning
confidence: 99%
“…Research results showed that short-term aerobic exercise training caused no significant change in serum leptin level (3). While other studies showed that extreme physical activity may lead to a decrease in leptin concentration due to a decrease in weight and fat mass (4). However, there are insufficient research findings to show that short-term exercise (less than 12 weeks) have any significant effect on leptin unless when the exercise is linked to fat mass reduction (2,5).…”
Section: Introductionmentioning
confidence: 97%